2014
DOI: 10.1071/mu12122
|View full text |Cite
|
Sign up to set email alerts
|

Threats from introduced birds to native birds

Abstract: Abstract. Invasion by introduced species is a global threat to the natural environment, with major consequences for biodiversity, economies and societies. This paper reviews the literature documenting interactions between introduced and native bird species. Surprisingly, we found only ten cases of an introduced bird being involved in a process that threatened a population of a native bird with extinction and conclude there is little evidence that introduced birds are a major threat to avian diversity globally.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 84 publications
(121 reference statements)
0
71
0
1
Order By: Relevance
“…A recent global review of alien bird impacts on native biodiversity, undertaken using a new protocol developed to quantify and categorise the impacts of alien species (the Environmental Impact Classification for Alien Taxa (EICAT); Hawkins et al 2015), could not find any impact data for 296 of 415 species ( 70%) with known alien populations (Evans et al 2016). Two other recent studies of the global impacts of alien birds (Baker et al 2014, Martin-Albarracin et al 2015 also found data for a relatively small number of species (33 and 39 respectively), and concluded that we need more information on their impacts. (Note that our usage of DD here differs from that of the IUCN Red List ( www.iucnredlist.org ), which relates to species extinction risk: 'A taxon is Data Deficient when there is inadequate information to make a direct, or indirect, assessment of its risk of extinction based on its distribution and/or population status.'…”
Section: Introductionmentioning
confidence: 98%
“…A recent global review of alien bird impacts on native biodiversity, undertaken using a new protocol developed to quantify and categorise the impacts of alien species (the Environmental Impact Classification for Alien Taxa (EICAT); Hawkins et al 2015), could not find any impact data for 296 of 415 species ( 70%) with known alien populations (Evans et al 2016). Two other recent studies of the global impacts of alien birds (Baker et al 2014, Martin-Albarracin et al 2015 also found data for a relatively small number of species (33 and 39 respectively), and concluded that we need more information on their impacts. (Note that our usage of DD here differs from that of the IUCN Red List ( www.iucnredlist.org ), which relates to species extinction risk: 'A taxon is Data Deficient when there is inadequate information to make a direct, or indirect, assessment of its risk of extinction based on its distribution and/or population status.'…”
Section: Introductionmentioning
confidence: 98%
“…Invasive alien species pose severe threats to biodiversity and ecosystem functioning (McGeoch et al 2010, Simberloff et al 2013, and birds have been assessed in this regard (Strubbe et al 2011, Baker et al 2014, MartinAlbarracin et al 2015. Their introductions can also be considered as 'unplanned' or 'imperfect' experiments that can be used to test eco-evolutionary hypotheses (Sax et al 2007).…”
Section: Assessing Invasive Birdsmentioning
confidence: 99%
“…Peacock et al 2007;Bonter et al 2010). The creating of novel niches brought about by anthropogenic change to the environment and urbanisation, and the factors indicated above, suggest that in the absence of humans these invasions would be unlikely or impossible (Gurevitch and Padilla 2004;Peacock et al 2007;Strubbe and Matthysen 2009 is little evidence that introduced birds are a major threat to avian biodiversity (Koenig 2003;Baker et al 2014). Currently in South Africa the main concern, if any, is highlighted by the expansion of Rose-ringed Parakeets, although, in time, other species may need to be monitored.…”
Section: Resultsmentioning
confidence: 97%
“…Pell and Tidemann 1997;Strubbe and Matthysen 2007;Lowe et al 2011;Czajka et al 2011;Newson et al 2011;Simberloff et al 2013;Baker et al 2014). The purpose of this paper is not to address these issues, where the impact of invasive species varies from those that benefit local biodiversity, e.g.…”
Section: Resultsmentioning
confidence: 98%